2015
DOI: 10.1002/rra.2881
|View full text |Cite
|
Sign up to set email alerts
|

Downstream Migration of the European Eel (Anguilla Anguilla) in the Elbe River, Germany: Movement Patterns and the Potential Impact of Environmental Factors

Abstract: Recruitment of European eels (Anguilla anguilla) has declined to the extent that they have been added to the IUCN Red List of Threatened Species. Therefore, it is critical to ensure that eels complete their outward river migration in order to contribute to the available spawning stock. We conducted a 4-year (2007)(2008)(2009)(2010)(2011) telemetry study to understand the migratory behaviour and potential impact of environmental factors on the eel during this critical life stage.Out of 399 female eels tagged wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 45 publications
4
37
0
Order By: Relevance
“…A possible interpretation of migration patterns shown here, which has been raised by other studies, is that sea migration could be a two‐step migration process (Durif et al , ; Aarestrup et al , ; Béguer‐Pon et al , ; Stein et al , ). It has been reported that A .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible interpretation of migration patterns shown here, which has been raised by other studies, is that sea migration could be a two‐step migration process (Durif et al , ; Aarestrup et al , ; Béguer‐Pon et al , ; Stein et al , ). It has been reported that A .…”
Section: Discussionmentioning
confidence: 99%
“…Crook et al () demonstrated extended estuarine residence time for Anguilla australis Richardson 1841, highlighting the possibility of more complex migration behaviour instead of the rapid and direct seaward migration originally assumed. Stein et al () also highlighted the possibility that A . anguilla may need more than one migratory season to reach the sea and may temporally revert to a non‐migratory stage.…”
Section: Discussionmentioning
confidence: 99%
“…The observed surgical infection rate (8%) and the associated mortality (2.65%) were in the range of reported values for the method used (Baras & Jeandrain, ). In general, implantation of telemetry transmitters has been shown to have little effect on the survival rate of eels (Simon, Berends, Dorner, Jepsen & Fladung, ; Stein et al., , Winter, Jansen, Adam & Schwevers, ), but possible surgically induced death after recovery and release could not be excluded (Stein et al., ). An activity‐reducing effect within the first 11 weeks after tagging and release has also been demonstrated (Winter et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Stein et al. () observed that the animals had to be kept for more than 20 days to terminate the migration of all the eels tested and that the rate of continuation of migration was highest after caging for up to 10 days. The reversal rate in the Warnow River after the first release was 21%, and 11% after recapture and re‐release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation